Outcomes of standardised approach to metabolic bone disease of prematurity. (2nd January 2018) - Chin, Lit Kim; Doan, John; Teoh, Yvonne SL; Stewart, Alice; Forrest, Peter; Simm, Peter J
Abstract : Aim: To assess the current protocol of metabolic bone disease (MBD) at three Monash Health neonatal units (Melbourne, Australia). Methods: Retrospective audit of 171 infants born at <32 weeks' gestation over 18 months. Mean gestational age was 28.6 ± 2.1 weeks, and birthweight was 1190 ± 374 g. Risk factors of MBD include intra‐uterine growth retardation ( n = 33, 19.3%), maternal pre‐eclampsia ( n = 17, 9.9%), necrotising enterocolitis ( n = 9, 5.4%) and medications like methylxanthines (94.2%; mean 54.8 days), diuretics (38.6%; mean 49.2 days) and glucocorticoids (5.3%; mean 35 days). Results: In total, 84.8% infants had an initial MBD screen (mean age 36.3 days), with 45% having repeated monitoring (mean age 71.9 days), and 14.2% had initial alkaline phosphatase levels >500 U/L, decreasing to 10.1% on follow‐up. All infants received additional vitamin D supplementation of 400 IU/day, phosphate of 25.1% ( n = 43) and calcium of 19.9% ( n = 34). Fractures were identified from clinical documentation in 2.9% ( n = 5) of infants. Stratifying into phosphate‐treated and untreated groups revealed significant differences ( P < 0.001) for gestational age and birthweight: 26.7 ± 1.7 weeks/918 ± 272 g for treated versus 29.2 ± 1.9 weeks/1283 ± 359 g for untreated. In the phosphate‐treated group, improvement was seen in mean alkaline phosphatase (pre‐treatment 467 ± 204 U/L and post‐treatment 342 ± 221 U/L, P < 0.01) and mean phosphate levels (1.8 ± 0.4 vs. 2.2 ± 1.0 mmol/L, P < 0.01). Linear growth difference between phosphate‐treated ( n = 10) and untreated groups ( n = 24) was insignificant at >6 months of age ( P = 0.13), although this may reflect limited data. Conclusion: Adequate first‐line supplementation with vitamin D and phosphate appeared to improve biochemical markers of MBD, but given the observational nature of this study, further longitudinal/prospective studies are required to confirm these findings.